Combinatorial patterns in medical case reports: an English-Spanish contrastive analysis - Mendez-Cendon, Beatriz (The Journal of Specialised Translation, 2009)
There have been several studies related to the description of phraseological and rhetorical structures in specific types of medical prose genres. However, to our knowledge, these studies have never focused on combinatorial patterns and have never been interlinguistic. In this paper we analyse the phraseological patterns of medical case reports published in journals and online forums. It is our purpose to identify Spanish and English combinatorial patterns which are recurrent in the discourse of this text genre so as to establish intralinguistic and interlinguistic equivalences among them. We also account for the role phraseological patterns play in the building of information in case reports and in the communicative aim of this genre. We firmly believe that knowing the phraseological practices of the genre and its internal ordering of information is essential to produce coherent and readable target texts.